2007
DOI: 10.1364/josab.24.002268
|View full text |Cite
|
Sign up to set email alerts
|

Numerical optimization of a grating coupler for the efficient excitation of surface plasmons at an Ag-SiO_2 interface

Abstract: The efficient generation of surface plasmons from free space optical waves is still an open problem in the field. Here we present a methodology and optimized design for a grating coupler. The photoexcitation of surface plasmons at an Ag-SiO 2 interface is numerically demonstrated to yield greater than 50% coupling from a Gaussian beam into surface plasmon voltages and currents.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 17 publications
2
47
0
Order By: Relevance
“…Using a hierarchal search optimization algorithm, varying the width and position of 14 grooves the authors achieved an excitation efficiency of 50%, which is the highest efficiency reported in the literature for a grating coupler. In the present paper we extend the work of Lu et al [11] to allow free shapes and topologies of the groves and we study not only the case of coupling into the plasmon but also the coupling of light from the plasmon into the dielectric surroundings. By increasing the design freedom using the topology optimization method we manage to improve the coupling efficiency from 50% reported by Lu et al [11] to more than 68% which is obtained for a coupling topology with slanted groves.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Using a hierarchal search optimization algorithm, varying the width and position of 14 grooves the authors achieved an excitation efficiency of 50%, which is the highest efficiency reported in the literature for a grating coupler. In the present paper we extend the work of Lu et al [11] to allow free shapes and topologies of the groves and we study not only the case of coupling into the plasmon but also the coupling of light from the plasmon into the dielectric surroundings. By increasing the design freedom using the topology optimization method we manage to improve the coupling efficiency from 50% reported by Lu et al [11] to more than 68% which is obtained for a coupling topology with slanted groves.…”
Section: Introductionmentioning
confidence: 93%
“…We use the material and geometry settings from [11]. The computational models for the input and output couplers are presented in Figs.…”
Section: Topology Optimization Of Two-dimensional Surface Plasmon Gramentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, we tested a large number of local and global optimization algorithms implemented in the free optimization package NLopt [48] and found that direct application of the algorithms generally yield suboptimal results. Therefore, we employ a step-wise search strategy [49,50]: starting from vacuum, we add components one by one. At each step, a global optimization is performed to find parameters of the new component, followed by a gradient-based local optimization on the parameters of all components.…”
Section: Optimizationmentioning
confidence: 99%